Before/during/after [videorecording (DVD)] - Steeves, Finnerty; Steeves, Finnerty; Davidson, Jeremy; Pankow, John; Sutherland, Kristine, 1958-; Conlee, John Ellison, 1968-; Blackwell, Susan; Masur, Richard (Gravitas Ventures, 2021)
A middle-aged NYC theatre actress figures out the kind of person she wants to be when her seemingly perfect fifteen-year marriage comes to an end.